Autonomous Low-Thrust Guidance: Application to SMART-1 and BepiColombo - GIL-FERNÁNDEZ, JESÚS; GRAZIANO, MARIELLA; GÓMEZ-TIERNO, M A; MILIC, E (Annals of the New York Academy of Sciences, 2004)
: Several techniques have been developed to obtain optimum trajectories with low‐thrust propulsion. However, few low‐thrust guidance schemes have been investigated to fly the reference optimum trajectories. The guidance algorithm successfully employed in the DeepSpace1 mission was the first approximation through the presented guidance schemes, valid for various interplanetary low‐thrust trajectories, independently of the optimization technique they result from. A method is presented to transform any given thrust profile to a thrust law defined by a finite set of control variables. This law allows the definition of a control vector to be optimized for the guidance purposes. Simulations were carried out to compare the performances of the algorithms to very different missions, such as SMART‐1 and BepiColombo. The good performance of the enhanced guidance schemes prove the generic applicability of the algorithm. Parametric analysis allows the assessment of stability and robustness of the schemes and the sensitivity to certain parameters.